(untitled) (Journal of the College of Basic Education, 2024)
The current research aims to identify the impact of the guided imagination strategy on the development of reflective thinking and to reveal the size of the impact of the strategy on the development of reflective thinking in the subject of analysis and artistic criticism. Reflective Thinking Dimensionally The other null hypothesis is related to the difference between the mean scores of the experimental group students in the (pre-post) scale of reflective thinking. The research was limited to fifth-grade (morning) students at the Institute of Fine Arts for Girls in the General Directorate of Education in Baghdad/Al-Karkh I for the academic year (2022-2023) in the subject of analysis and artistic criticism. The researcher adopted the experimental method, as she used an experimental design with partial control (the design of the experimental and control groups with a pre- and post-test). The research sample consisted of (12) female students distributed into two groups, (6) female students in the experimental group and (6) female students in the control group. The results of the research showed that the female students of the experimental group were superior to the female students of the control group in the reflective thinking scale. In light of the results, the researcher recommended working to increase interest in modern teaching models that help develop mental abilities when asked. The researcher suggested conducting a similar study to find out the effect of the wave imagination strategy in solving problems. the problems.